PVC wear-resistant cable with double modified protective layers
By using a double-modified protective layer in the cable and combining the crosslinking technology of KH570 modified graphene and fluororesin, the problems of wear and cracking of the protective layer during use are solved, and the wear resistance and service life are significantly improved.
Patent Information
- Application Number
- CN202411870565.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
During use, the cable is susceptible to heavy objects crushing and friction, resulting in surface wear and cracking of the protective layer, affecting the service life of the cable and the normal operation of the equipment.
PVC wear-resistant cable with double-modified protective layer is used, including conductor core, insulating layer, shielding layer, flame retardant layer and double-modified protective layer. The double-modified protective layer consists of PVC, plasticizer, graphene fluororesin composite powder, POE toughening resin, stabilizer, lubricant and antioxidant. The KH570 modified graphene is crosslinked with the fluororesin to form chemical connections, improving dispersion and migration ability.
It significantly improves the wear resistance and service life of the cable, reduces the degree of wear, ensures the physical impact resistance of the cable during installation, operation and transfer, and ensures the normal operation of the equipment.
Smart Images

Figure CN119650154A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable products, and in particular relates to a PVC wear-resistant cable with a double modified protective layer. Background Art
[0002] Cables are easily crushed by heavy objects, rubbed by friction and other forces during use. At the same time, during the movement and vibration of instruments and equipment, the cables connected to them will inevitably be hit and impacted. These forces may cause wear on the cable surface and even cracking of the surface protective layer, thus affecting the service life of the cable and the normal operation of the equipment. Therefore, the wear resistance of the cable sheath as the outermost protective layer is particularly important. This is related to whether the cable can effectively resist external physical impacts during installation, operation and transfer, so as to ensure its own integrity and service life and the normal operation of the corresponding power system. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a PVC wear-resistant cable with a double modified protective layer, comprising a conductor core, an insulating layer, a shielding layer, a flame retardant layer, and a double modified protective layer, wherein the conductor core, the insulating layer, the shielding layer, and the flame retardant layer are coaxially and closely arranged from the inside to the outside in sequence to form a functional core material, and the double modified protective layer is coated on the outside of one or more functional core materials to form a cable.
[0004] The double modified protective layer is calculated by weight, including 100 parts of PVC, 20-40 parts of plasticizer, 10-20 parts of graphene fluororesin composite powder, 5-15 parts of POE toughening resin, 3-4 parts of stabilizer, 2-4 parts of lubricant, and 1-2 parts of antioxidant.
[0005] The graphene-fluororesin composite powder is calculated by weight and includes 100 parts of fluororesin, 1 to 2 parts of a cross-linking agent, and 10 to 15 parts of KH570 modified graphene.
[0006] Preferably, more than two functional core materials are twisted together, and the gaps between the functional core materials on the inner side of the double modified protective layer are filled with filling ropes.
[0007] Furthermore: the functional core material and the filling rope that are concentrated together are tightly wrapped by the non-woven fabric layer as a whole, and the double modified protective layer is coaxially tightly wrapped outside the non-woven fabric layer.
[0008] Preferably, the preparation method of KH570 modified graphene is as follows: at room temperature (25°C, the same below), graphene oxide is fully ultrasonically dispersed in deionized water at a concentration of 1 to 10 mg / mL, and then, under stirring, an ethanol dispersion of KH570 (γ-methacryloxypropyltrimethoxysilane) with a mass concentration of 10 to 15 mg / mL is added dropwise at a mass ratio of KH570 to graphene oxide of 5 to 20:1. After the addition is completed, the temperature is raised to 80 to 85°C and refluxed for 5 to 7 hours, then the temperature is lowered to room temperature, and the solid precipitate is fully washed after centrifugation and then centrifuged and dried at 70 to 80°C to obtain KH570 modified graphene.
[0009] Preferably, the plasticizer is dioctyl phthalate (DOP), dioctyl terephthalate (DOTP), diisodecyl phthalate (DIDP), or the like.
[0010] As a preferred stabilizer, zinc stearate, magnesium stearate, calcium stearate, etc.
[0011] Preferably, the lubricant is zinc stearate, calcium stearate, polyethylene wax or the like.
[0012] Preferably, the antioxidant is antioxidant 1010, antioxidant 1076, antioxidant 245, etc.
[0013] Preferably, the crosslinking agent is a peroxide crosslinking agent, such as dicumyl peroxide.
[0014] Preferably, the preparation method of the graphene fluororesin composite powder is to fully stir and mix the fluororesin, the cross-linking agent and the KH570 modified graphene, add the mixture into an extruder for blending, extrusion and granulation, and crush the mixture into 200-300 meshes by liquid nitrogen.
[0015] Preferably, the preparation method of the double-modified protective layer is to fully stir and mix PVC, plasticizer, graphene fluororesin composite powder, POE toughening resin, stabilizer, lubricant and antioxidant, add them into an extruder for blending, extrusion and granulation as a double-modified protective layer masterbatch, and then extrude the obtained double-modified protective layer masterbatch into shape.
[0016] As a preferred embodiment, the preparation operation of the cable is as follows: after the insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core, and after cooling, an insulating layer tightly wrapped on the conductor core is formed; a strip-shaped shielding cloth is evenly and tightly wrapped around the outside of the insulating layer as a shielding layer coaxially arranged with the insulating layer; a strip-shaped flame-retardant cloth is evenly and tightly wrapped around the outside of the shielding layer as a flame-retardant layer coaxially arranged with the shielding layer; the conductor core, the insulating layer, the shielding layer, and the flame-retardant layer together constitute a functional core material, all the functional core materials and the filling ropes for filling the gaps are parallel to each other and concentrated together and then twisted, and then the twisted functional core materials and filling ropes are uniformly and tightly wrapped with non-woven fabric as a whole, so as to form a non-woven fabric layer; after the double-modified protective layer masterbatch is melted in an extruder, it is evenly extruded on the non-woven fabric layer, and after cooling, a double-modified protective layer coaxially and tightly wrapped around the non-woven fabric layer is formed,
[0017] The filling rope is fluffy and elastic in its natural state. Therefore, during the concentrated twisting and non-woven fabric wrapping process, the filling rope is further squeezed by the functional core material or the non-woven fabric, and thus the gaps can be substantially filled.
[0018] The beneficial effects of the present invention are as follows: KH570 is firstly hydrolyzed and then grafted onto the surface of graphene to make the surface of graphene have carbon-carbon double bonds, and then the graphene and fluororesin are co-extruded and cross-linked to make the carbon-carbon double bonds on the graphene participate in the cross-linking reaction of the fluororesin molecular chain, thereby chemically connecting the graphene and the fluororesin together.
[0019] Before the graphene fluororesin composite material is added to the PVC resin matrix as a wear-resistant filler for extrusion molding, the graphene fluororesin composite material masterbatch is further liquid nitrogen crushed to a smaller particle size, which can greatly promote the dispersion of graphene fluororesin in the product and facilitate its migration to the surface of the product; at the same time, based on the synergistic effect between graphene and fluororesin: on the one hand, there is a significant difference in surface energy between fluororesin and PVC matrix resin, so fluororesin itself has a tendency to migrate to the surface of the product; on this basis, graphene fillers are stably distributed on the cross-linked molecular network structure of fluororesin, and graphene produces a certain steric effect on the molecular network, so that the molecular network maintains a certain unfolding state, avoids excessive curling, and is conducive to the absorption of external heat by the entire molecular network. At the same time, these graphenes also have strong heat absorption, which can quickly absorb and transfer the heat of extrusion processing to various parts of the fluororesin cross-linked network, so that the local activity of various parts of the fluororesin cross-linked network is enhanced at the same time, which is greatly conducive to the migration of the fluororesin cross-linked network in the matrix. It can be seen that the migration of fluororesin to the surface of the product is also closely related to the graphene material chemically bonded to the fluororesin.
[0020] Finally, after the fluororesin migrates to the surface of the product, it also brings more graphene to the surface of the protective layer. In this way, not only does the fluororesin help reduce the surface energy of the product and reduce the degree of wear when the product is subjected to external friction, but at the same time, the graphene precipitates on the surface of the product, and its two-dimensional layered structure enables it to form a lubricating film during the friction process, reducing the friction load, thereby reducing wear and tear, and also playing a wear-resistant and friction-reducing effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the multilayer structure of the PVC wear-resistant cable with double modified protective layers of the present invention (radial cross-sectional view),
[0022] Among them, 1 is the conductor core, 2 is the insulation layer, 3 is the shielding layer, 4 is the flame retardant layer, 5 is the double modified protective layer, 6 is the filling rope, and 7 is the non-woven fabric layer. DETAILED DESCRIPTION
[0023] Example 1
[0024] (1) At room temperature, 1000 g of graphene oxide was added into 800 L of deionized water and dispersed thoroughly by ultrasonication to obtain a graphene oxide dispersion;
[0025] At room temperature, 8000 g of KH570 was added into 800 L of anhydrous ethanol and dispersed thoroughly by ultrasonication to obtain a KH570 dispersion.
[0026] After adding the graphene oxide dispersion prepared in this example to a reactor, the KH570 dispersion prepared in this example was added dropwise thereto under stirring at room temperature. After the addition was completed in 30 minutes, the mixed system in the reactor was heated to about 83° C. and kept under reflux for 5 hours, then cooled to room temperature, and solid precipitates were collected after centrifugation, and the precipitates were fully washed, centrifuged, and dried at 70° C. to obtain KH570 modified graphene.
[0027] Calculated by weight, 100 parts of polyvinylidene fluoride (710, the same below), 1 part of diisopropylbenzene peroxide, 1 part of zinc stearate, and 15 parts of the KH570 modified graphene prepared above are added to a high-speed mixer and fully stirred and mixed, and then added to a twin-screw extruder at 165-200°C (165°C for zone 1, 180°C for zone 2, 190°C for zone 3, 200°C for zone 4, 200°C for zone 5, 195°C for die, 25:1 for screw aspect ratio, 300 rpm for screw speed, the same below) for extrusion and granulation, and the obtained granules are crushed to 240-300 meshes in a liquid nitrogen crusher to serve as graphene fluororesin composite powder;
[0028] (2) Calculated by weight, 100 parts of PVC (type SG-3, the same below), 35 parts of dioctyl terephthalate, 16 parts of graphene fluororesin composite powder prepared in step (1), 12 parts of POE toughening resin (8100, the same below), 3 parts of zinc stearate, 3 parts of polyethylene wax (molecular weight 5000, the same below), and 1.5 parts of antioxidant 1076 are added to a high-speed mixer and stirred and mixed thoroughly, and then added to a twin-screw extruder at 145-180°C (zone 1 is set at 145°C, zone 2 is set at 155°C, zone 3 is set at 165°C, zone 4 is set at 175°C, zone 5 is set at 180°C, die is set at 175°C, screw aspect ratio is 18:1, screw speed is 150rpm, the same below) for extrusion and granulation to obtain a double modified protective layer masterbatch;
[0029] (3) After a conventional insulating layer masterbatch available on the market is melted in an extruder, it is coaxially extruded onto the outer surface of a conductor core (1) (formed by twisting a plurality of round copper wires, the same below), and after cooling, an insulating layer (2) tightly covering the conductor core (1) is formed; an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer (2) to form a shielding layer (3) coaxially arranged with the insulating layer (2); a flame-retardant mica tape is evenly and tightly wrapped around the shielding layer (3) to form a flame-retardant layer (4) coaxially arranged with the shielding layer (3); the conductor core (1), the insulating layer (2), the shielding layer (3), and the flame-retardant layer (4) together constitute a functional core material, and seven such functional core materials and a plurality of filling ropes (6) for filling the gaps between these functional core materials are fully coordinated and concentrated together in parallel (wherein, in terms of the arrangement of the functional core materials, The inner side is one and the outer side is uniformly and tightly surrounded by six) and then twisted, and then the functional core material and the filling rope (6) twisted together are used as a whole, and are uniformly and tightly wrapped with non-woven fabric to form a non-woven fabric layer (7); the double-modified protective layer masterbatch prepared in step (2) of this embodiment is melted and uniformly extruded on the non-woven fabric layer (7) in an extruder at 145-180°C (zone 1 is set at 145°C, zone 2 is set at 155°C, zone 3 is set at 165°C, zone 4 is set at 175°C, zone 5 is set at 180°C, the die is set at 175°C, the screw aspect ratio is 18:1, the screw speed is 150rpm, the same below), and after cooling, a double-modified protective layer (5) coaxially and tightly wrapping the non-woven fabric layer (7) is formed (the thickness of the formed double-modified protective layer is 1.8 mm, the same below).
[0030] Example 2
[0031] (1) At room temperature, 1000 g of graphene oxide was added to 500 L of deionized water and dispersed thoroughly by ultrasonication to obtain a graphene oxide dispersion;
[0032] At room temperature, 5000 g of KH570 was added into 400 L of anhydrous ethanol and dispersed thoroughly by ultrasonication to obtain a KH570 dispersion.
[0033] After adding the graphene oxide dispersion prepared in this example to the reactor, the KH570 dispersion prepared in this example was added dropwise thereto under stirring at room temperature. After 15 minutes of complete addition, the mixed system in the reactor was heated to about 82° C. and kept at reflux for 5 hours, then cooled to room temperature, and solid precipitates were collected after centrifugation, and the precipitates were fully washed, centrifuged, and dried at 75° C. to obtain KH570 modified graphene.
[0034] Calculated by weight, 100 parts of polyvinylidene fluoride, 1.3 parts of diisopropylbenzene peroxide, 1 part of lead stearate, and 15 parts of the KH570 modified graphene prepared above are added to a high-speed mixer and fully stirred and mixed, and then added to a twin-screw extruder for extrusion and granulation at 165-200° C., and the obtained pellets are crushed to 240-300 meshes in a liquid nitrogen crusher to serve as graphene fluororesin composite powder;
[0035] (2) Calculated by weight, 100 parts of PVC, 30 parts of dioctyl phthalate, 10 parts of the graphene fluororesin composite powder prepared in step (1), 15 parts of POE toughening resin, 4 parts of calcium stearate, 4 parts of polyethylene wax, and 2 parts of antioxidant 1076 are added to a high-speed mixer and stirred thoroughly, and then added to a twin-screw extruder for extrusion at 145-180° C. and granulation to obtain a double-modified protective layer masterbatch;
[0036] (3) After a conventional insulating layer masterbatch available on the market is melted in an extruder, it is coaxially extruded onto the outer surface of a conductor core (1), and after cooling, an insulating layer (2) is formed that is tightly wrapped around the conductor core (1); an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer (2) to form a shielding layer (3) that is coaxially arranged with the insulating layer (2); a flame-retardant mica tape is evenly and tightly wrapped around the shielding layer (3) to form a flame-retardant layer (4) that is coaxially arranged with the shielding layer (3); the conductor core (1), the insulating layer (2), the shielding layer (3), and the flame-retardant layer (4) together constitute a functional core material, and seven such functional core materials and a material for filling these functional core materials are placed on the surface of the functional core material. A plurality of filling ropes (6) in the gaps between the core materials are parallel to each other and fully matched and concentrated together (wherein, in terms of the arrangement of the functional core material, there is one rope inside and six ropes are evenly and tightly arranged in a circular shape outside) and then twisted together. Then, the evenly twisted functional core material and the filling ropes (6) are taken as a whole and evenly and tightly wrapped with a non-woven fabric to form a non-woven fabric layer (7); the double-modified protective layer masterbatch prepared in step (2) of this embodiment is melted and evenly extruded on the non-woven fabric layer (7) at 145-180° C. in an extruder, and after cooling, a double-modified protective layer (5) coaxially and tightly wrapping the non-woven fabric layer (7) is formed.
[0037] Example 3
[0038] (1) At room temperature, 1000 g of graphene oxide was added into 200 L of deionized water and dispersed thoroughly by ultrasonication to obtain a graphene oxide dispersion;
[0039] At room temperature, 12000 g of KH570 was added into 1200 L of anhydrous ethanol and dispersed thoroughly by ultrasonication to obtain a KH570 dispersion.
[0040] After adding the graphene oxide dispersion prepared in this example to a reactor, the KH570 dispersion prepared in this example was added dropwise thereto under stirring at room temperature. After the addition was completed in 50 minutes, the mixed system in the reactor was heated to about 85° C. and kept at reflux for 5 hours, then cooled to room temperature, and solid precipitates were collected after centrifugation, and the precipitates were fully washed, centrifuged, and dried at 78° C. to obtain KH570 modified graphene.
[0041] Calculated by weight, 100 parts of polyvinylidene fluoride, 1.2 parts of diisopropylbenzene peroxide, 2 parts of zinc stearate, and 10 parts of the KH570 modified graphene prepared above are added to a high-speed mixer and fully stirred and mixed, and then added to a twin-screw extruder for extrusion and granulation at 165-200° C., and the obtained pellets are crushed to 240-300 meshes in a liquid nitrogen crusher to serve as graphene fluororesin composite powder;
[0042] (2) Calculated by weight, 100 parts of PVC, 40 parts of diisodecyl phthalate, 20 parts of the graphene fluororesin composite powder prepared in step (1), 10 parts of POE toughening resin, 4 parts of zinc stearate, 4 parts of polyethylene wax, and 1 part of antioxidant 1010 are added to a high-speed mixer and stirred thoroughly, and then added to a twin-screw extruder for extrusion at 145-180° C. and granulation to obtain a double-modified protective layer masterbatch;
[0043] (3) After a conventional insulating layer masterbatch available on the market is melted in an extruder, it is coaxially extruded onto the outer surface of a conductor core (1), and after cooling, an insulating layer (2) is formed that is tightly wrapped around the conductor core (1); an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer (2) to form a shielding layer (3) that is coaxially arranged with the insulating layer (2); a flame-retardant mica tape is evenly and tightly wrapped around the shielding layer (3) to form a flame-retardant layer (4) that is coaxially arranged with the shielding layer (3); the conductor core (1), the insulating layer (2), the shielding layer (3), and the flame-retardant layer (4) together constitute a functional core material, and seven such functional core materials and a material for filling these functional core materials are placed on the surface of the functional core material. A plurality of filling ropes (6) in the gaps between the core materials are parallel to each other and fully matched and concentrated together (wherein, in terms of the arrangement of the functional core material, there is one rope inside and six ropes are evenly and tightly arranged in a circular shape outside) and then twisted together. Then, the evenly twisted functional core material and the filling ropes (6) are taken as a whole and evenly and tightly wrapped with a non-woven fabric to form a non-woven fabric layer (7); the double-modified protective layer masterbatch prepared in step (2) of this embodiment is melted and evenly extruded on the non-woven fabric layer (7) at 145-180° C. in an extruder, and after cooling, a double-modified protective layer (5) coaxially and tightly wrapping the non-woven fabric layer (7) is formed.
[0044] Comparative Example 1
[0045] The graphene oxide was not grafted with KH570, and the remaining components and operations were the same as those in Example 1:
[0046] (1) Calculated by weight, 100 parts of polyvinylidene fluoride, 1 part of diisopropylbenzene peroxide, 1 part of zinc stearate, and 15 parts of graphene oxide are added to a high-speed mixer and stirred and mixed thoroughly, and then added to a twin-screw extruder for extrusion and granulation at 165-200° C., and the obtained granules are crushed in a liquid nitrogen crusher to 240-300 meshes to obtain a graphene fluororesin composite powder;
[0047] (2) Calculated by weight, 100 parts of PVC, 35 parts of dioctyl terephthalate, 16 parts of the graphene fluororesin composite powder prepared in step (1), 12 parts of POE toughening resin, 3 parts of zinc stearate, 3 parts of polyethylene wax, and 1.5 parts of antioxidant 1076 are added to a high-speed mixer and stirred thoroughly, and then added to a twin-screw extruder for extrusion at 145-180° C. and granulation to obtain a double-modified protective layer masterbatch;
[0048] (3) After a conventional insulating layer masterbatch available on the market is melted in an extruder, it is coaxially extruded onto the outer surface of a conductor core (1), and after cooling, an insulating layer (2) is formed that is tightly wrapped around the conductor core (1); an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer (2) to form a shielding layer (3) that is coaxially arranged with the insulating layer (2); a flame-retardant mica tape is evenly and tightly wrapped around the shielding layer (3) to form a flame-retardant layer (4) that is coaxially arranged with the shielding layer (3); the conductor core (1), the insulating layer (2), the shielding layer (3), and the flame-retardant layer (4) together constitute a functional core material, and seven such functional core materials and a material for filling these functional cores are placed on the surface of the functional core material. A plurality of filling ropes (6) in the gaps between the functional core materials are fully matched and concentrated together in parallel (wherein, in terms of the arrangement of the functional core material, there is one rope on the inner side and six ropes on the outer side are uniformly and tightly arranged in a circular shape) and then twisted together, and then the functional core material and the filling ropes (6) uniformly twisted together are used as a whole and are uniformly and tightly wrapped with a non-woven fabric to form a non-woven fabric layer (7); the double-modified protective layer masterbatch prepared in step (2) of this comparative example is melted and uniformly extruded on the non-woven fabric layer (7) at 145-180° C. in an extruder, and after cooling, a double-modified protective layer (5) coaxially and tightly wrapping the non-woven fabric layer (7) is formed.
[0049] Comparative Example 2
[0050] The graphene oxide was not grafted with KH570 but directly added to PVC. The fluororesin was not crosslinked and extruded but directly added to PVC. The other components and operations were the same as those in Example 1.
[0051] (1) Calculated by weight, 100 parts of PVC, 35 parts of dioctyl terephthalate, 13.7 parts of polyvinylidene fluoride, 2.1 parts of graphene oxide, 12 parts of POE toughening resin, 3.1 parts of zinc stearate, 3 parts of polyethylene wax, and 1.5 parts of antioxidant 1076 were added to a high-speed mixer and stirred thoroughly, and then added to a twin-screw extruder for extrusion and granulation at 145-180°C to obtain a double-modified protective layer masterbatch;
[0052] (2) After a conventional insulating layer masterbatch available on the market is melted in an extruder, it is coaxially extruded onto the outer surface of a conductor core (1), and after cooling, an insulating layer (2) tightly covering the conductor core (1) is formed; an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer (2) to form a shielding layer (3) coaxially arranged with the insulating layer (2); a flame-retardant mica tape is evenly and tightly wrapped around the shielding layer (3) to form a flame-retardant layer (4) coaxially arranged with the shielding layer (3); the conductor core (1), the insulating layer (2), the shielding layer (3), and the flame-retardant layer (4) together constitute a functional core material, and seven such functional core materials and a material for filling these functional cores are placed on the functional core material. A plurality of filling ropes (6) in the gaps between the functional core materials are fully matched and concentrated together in parallel (wherein, in terms of the arrangement of the functional core material, there is one rope on the inner side and six ropes on the outer side are uniformly and tightly arranged in a circular shape) and then twisted together, and then the functional core material and the filling ropes (6) uniformly twisted together are used as a whole and are uniformly and tightly wrapped with a non-woven fabric to form a non-woven fabric layer (7); the double-modified protective layer masterbatch prepared in step (1) of this comparative example is melted and uniformly extruded on the non-woven fabric layer (7) at 145-180° C. in an extruder, and after cooling, a double-modified protective layer (5) coaxially and tightly wrapping the non-woven fabric layer (7) is formed.
[0053] Comparative Example 3
[0054] In step (1), the graphene fluororesin masterbatch after extrusion and granulation is not crushed, and the remaining components and operations are the same as those in Example 1:
[0055] (1) At room temperature, 1000 g of graphene oxide was added into 800 L of deionized water and dispersed thoroughly by ultrasonication to obtain a graphene oxide dispersion;
[0056] At room temperature, 8000 g of KH570 was added into 800 L of anhydrous ethanol and dispersed thoroughly by ultrasonication to obtain a KH570 dispersion.
[0057] After adding the graphene oxide dispersion prepared in this comparative example into a reactor, the KH570 dispersion prepared in this example was added dropwise thereto under stirring at room temperature. After the addition was completed in 30 minutes, the mixed system in the reactor was heated to about 83° C. and kept under reflux for 5 hours, then cooled to room temperature, and solid precipitates were collected after centrifugation, and the precipitates were fully washed, centrifuged, and dried at 70° C. to obtain KH570 modified graphene.
[0058] Calculated by weight, 100 parts of polyvinylidene fluoride, 1 part of diisopropylbenzene peroxide, 1 part of zinc stearate, and 15 parts of the KH570 modified graphene prepared above are added to a high-speed mixer and fully stirred and mixed, and then added to a twin-screw extruder for extrusion at 165-200° C. and granulation (particle size is about 2 mm) to obtain a graphene fluororesin masterbatch;
[0059] (2) Calculated by weight, 100 parts of PVC, 35 parts of dioctyl terephthalate, 16 parts of the graphene fluororesin masterbatch prepared in step (1), 12 parts of POE toughening resin, 3 parts of zinc stearate, 3 parts of polyethylene wax, and 1.5 parts of antioxidant 1076 are added to a high-speed mixer and stirred thoroughly, and then added to a twin-screw extruder for extrusion at 145-180° C. and granulation to obtain a double-modified protective layer masterbatch;
[0060] (3) After a conventional insulating layer masterbatch available on the market is melted in an extruder, it is coaxially extruded onto the outer surface of a conductor core (1), and after cooling, an insulating layer (2) is formed that is tightly wrapped around the conductor core (1); an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer (2) to form a shielding layer (3) that is coaxially arranged with the insulating layer (2); a flame-retardant mica tape is evenly and tightly wrapped around the shielding layer (3) to form a flame-retardant layer (4) that is coaxially arranged with the shielding layer (3); the conductor core (1), the insulating layer (2), the shielding layer (3), and the flame-retardant layer (4) together constitute a functional core material, and seven such functional core materials and a material for filling these functional cores are placed on the surface of the functional core material. A plurality of filling ropes (6) in the gaps between the functional core materials are fully matched and concentrated together in parallel (wherein, in terms of the arrangement of the functional core material, there is one rope on the inner side and six ropes on the outer side are uniformly and tightly arranged in a circular shape) and then twisted together, and then the functional core material and the filling ropes (6) uniformly twisted together are used as a whole and are uniformly and tightly wrapped with a non-woven fabric to form a non-woven fabric layer (7); the double-modified protective layer masterbatch prepared in step (2) of this comparative example is melted and uniformly extruded on the non-woven fabric layer (7) at 145-180° C. in an extruder, and after cooling, a double-modified protective layer (5) coaxially and tightly wrapping the non-woven fabric layer (7) is formed.
[0061] According to the standard of GB / T 3960-2016 "Plastic Sliding Friction and Wear Test Method", the outermost double modified protective layer of the cable prepared in the above-mentioned embodiments and comparative embodiments was tested for wear to judge its wear resistance, wherein the friction mode was dry friction, the test ring speed was 200r / min, the test load was 200N, the test wear time lasted for 2 hours, and before the start of the wear test of each sample, it was ensured that the roughness Ra of the outer cylindrical surface of the test ring used for friction contact with the sample was 0.4. Three samples of the same product were tested and the average was taken, as shown in Table 1 (after the wear test, no obvious damage such as cracking and perforation was observed on the outer surface of the samples of each embodiment and comparative embodiment).
[0062] According to the standard of GB / T 2951 "General Test Methods for Insulation and Sheath Materials of Electric and Optical Cables", the mechanical properties of the outermost double modified protective layers of the cables prepared in the above embodiments and comparative embodiments were tested respectively, and three samples of the same product were tested and the average was taken. The details are shown in Table 1.
[0063] Table 1
[0064]
[0065] From Table 1, firstly, in Comparative Example 2, the graphene material is not chemically connected to the fluororesin, so when the fluororesin molecular segments migrate to the surface of the product in an uncross-linked state, the graphene material cannot be effectively brought close to the surface of the product, resulting in a decrease in wear resistance compared to Example 1.
[0066] In comparative example 3, according to conventional operation, the graphene fluororesin masterbatch was directly added to the matrix resin for co-extrusion without further sufficient crushing, and the final modification effect was very unsatisfactory. In this regard, the applicant believes that this is because after the cross-linking extrusion of the fluororesin (with the double-bond modified graphene), the molecular chains of the fluororesin form a chemical connection, and the combination is more stable, resulting in a significant decrease in its dispersibility in the matrix resin (even under the heating and shearing action of the extruder, it cannot be dispersed too effectively; and simply increasing the shear plasticization parameters of the screw will significantly increase the degradation of the matrix resin PVC). This agglomeration-like situation not only affects the mechanical properties, but also directly affects the migration ability of the fluororesin in the matrix resin, resulting in its wear resistance is also very unsatisfactory.
[0067] At the same time, the applicant also believes that the migration of fluororesin to the surface of the product is not only related to the above-mentioned dispersion degree when it enters the PVC extruder, but also has a great relationship with the graphene material chemically bonded to the fluororesin: in Comparative Example 1, in the case of no grafted graphene, although the single fluororesin masterbatch was also pre-treated by liquid nitrogen pulverization, from the wear resistance of the double-modified protective layer finally extruded, not only the graphene material freely dispersed in the matrix failed to effectively migrate close to the surface of the product, but even a considerable part of the fluororesin failed to effectively migrate close to the surface of the product, so its surface wear resistance has further declined compared with Comparative Example 1 where the fluororesin is not cross-linked. This is because in Comparative Example 1, the graphene oxide was not modified with carbon-carbon double bonds, so that the graphene material was not chemically connected and distributed on the cross-linked molecular network of the fluororesin, and the single fluororesin network tended to be more curled up, resulting in the heat during the extrusion process not being easy to fully enter the fluororesin network and be absorbed by it, resulting in insufficient activity of the fluororesin network and inability to achieve effective migration.
[0068] In this solution, although it is also a cross-linked fluororesin molecular network, the steric effect of graphene keeps the network in a relatively expanded state and prevents it from being too curled up. In addition, the excellent heat transfer properties of graphene allow heat to fully enter the molecular network, giving it good mobility and migration capabilities.
Claims
1. A PVC wear-resistant cable with a double modified protective layer, characterized in that: The cable comprises a conductor core (1), an insulating layer (2), a shielding layer (3), a flame retardant layer (4), and a double modified protective layer (5), wherein the conductor core (1), the insulating layer (2), the shielding layer (3), and the flame retardant layer (4) are coaxially and closely arranged from the inside to the outside in sequence to form a functional core material, and the double modified protective layer (5) is coated on one or more of the functional core materials to form the cable. The double modified protective layer (5) comprises, by weight, 100 parts of PVC, 20-40 parts of plasticizer, 10-20 parts of graphene fluororesin composite powder, 5-15 parts of POE toughening resin, 3-4 parts of stabilizer, 2-4 parts of lubricant, and 1-2 parts of antioxidant. The graphene-fluororesin composite powder comprises, by weight, 100 parts of fluororesin, 1 to 2 parts of a cross-linking agent, and 10 to 15 parts of KH570 modified graphene.
2. The PVC wear-resistant cable with double modified protective layers as claimed in claim 1, characterized in that: All of the functional core materials, two or more in number, are twisted together, and the gaps between the functional core materials inside the double modified protective layer (5) are filled with filling ropes (6).
3. The PVC wear-resistant cable with double modified protective layers as claimed in claim 2, characterized in that: The functional core material and the filling rope (6) gathered together are tightly wrapped by the non-woven fabric layer (7) as a whole, and the double modified protective layer (5) is coaxially and tightly wrapped outside the non-woven fabric layer (7).
4. The PVC wear-resistant cable with double modified protective layers as claimed in claim 1, characterized in that: The preparation method of the KH570 modified graphene is as follows: after dispersing graphene oxide in deionized water, KH570 dispersion is added dropwise thereto under stirring; after the addition is completed, the temperature is raised to 80-85° C. and refluxed for 5-7 hours, then the temperature is lowered to room temperature, and after centrifugation, the solid precipitate is fully washed, centrifuged, and dried to obtain the KH570 modified graphene.
5. The PVC wear-resistant cable with double modified protective layers as claimed in claim 1, characterized in that: The plasticizer is dioctyl phthalate, dioctyl terephthalate or diisodecyl phthalate.
6. The PVC wear-resistant cable with double modified protective layers as claimed in claim 1, characterized in that: The stabilizer is zinc stearate, magnesium stearate or calcium stearate; the lubricant is zinc stearate, calcium stearate or polyethylene wax; the antioxidant is antioxidant 1010, antioxidant 1076 or antioxidant 245; and the crosslinking agent is a peroxide crosslinking agent.
7. The PVC wear-resistant cable with double modified protective layers as claimed in claim 1, characterized in that: The preparation method of the graphene fluororesin composite powder is as follows: after fully stirring and mixing the fluororesin, the crosslinking agent and the KH570 modified graphene, adding them into an extruder for blending, extruding and granulating, and then crushing them into 200-300 meshes with liquid nitrogen.
8. The PVC wear-resistant cable with double modified protective layers as claimed in claim 1, characterized in that: The preparation method of the double-modified protective layer is to fully stir and mix the PVC, the plasticizer, the graphene fluororesin composite powder, the POE toughening resin, the stabilizer, the lubricant, and the antioxidant, add them into an extruder for blending, extrusion, and granulation to obtain a double-modified protective layer masterbatch, and then extrude the obtained double-modified protective layer masterbatch into shape.
9. The PVC wear-resistant cable with double modified protective layers as claimed in claim 3, characterized in that: The preparation operation of the cable is as follows: after the insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core (1), and after cooling, the insulating layer (2) is formed to be tightly wrapped on the conductor core (1); a strip-shaped shielding cloth is evenly and tightly wrapped around the insulating layer (2) to form a shielding layer (3) coaxially arranged with the insulating layer (2); a strip-shaped flame-retardant cloth is evenly and tightly wrapped around the shielding layer (3) to form a flame-retardant layer (4) coaxially arranged with the shielding layer (3); the conductor core (1), the insulating layer (2), the The shielding layer (3) and the flame retardant layer (4) together constitute the functional core material. All the functional core materials and the filling rope (6) used to fill the gap are parallel to each other and then twisted together. Then, the twisted functional core material and the filling rope (6) are evenly and tightly wrapped with non-woven fabric as a whole to form the non-woven fabric layer (7). The double-modified protective layer masterbatch is melted in an extruder and evenly extruded onto the non-woven fabric layer (7). After cooling, the double-modified protective layer (5) that coaxially and tightly wraps the non-woven fabric layer (7) is formed.
Citation Information
Cited By
Macromolecular polymeric material for plastic coating of metal wire and preparation method thereof
CN121447931A